2022
DOI: 10.1002/ptr.7538
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies of the antitumor effect of curcumin‐loaded polymeric nanocapsules: A systematic review and meta‐analysis

Abstract: Curcumin, a plant-derived compound, has various well-known biological effects (antiinflammatory, antioxidant, antitumor, among others) as well as some important limitations for formulators, such as poor water solubility and low oral bioavailability. Its nanoencapsulation is reported to overcome these drawbacks and to improve its in vivo efficacy. Here, data from preclinical in vivo studies evaluating the antitumor efficacy of curcumin-loaded polymeric nanocapsules are collected, analyzed, and discussed as a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Over the past several decades, nanoparticle-based delivery systems for curcumin have been tested both in vitro and in vivo, as well as in preclinical studies. Studies with nanoparticle-based delivery systems such as polymeric nanoparticles, lipid-based nanoparticles (NPs), nanogels, micelles, cyclodextrins, and silica nanoparticles have been carried out with limited efficacy [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, nanoparticle-based delivery systems for curcumin have been tested both in vitro and in vivo, as well as in preclinical studies. Studies with nanoparticle-based delivery systems such as polymeric nanoparticles, lipid-based nanoparticles (NPs), nanogels, micelles, cyclodextrins, and silica nanoparticles have been carried out with limited efficacy [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin exhibits anticancer properties, as demonstrated in a meta-analysis conducted by de Oliveira et al ( de Oliveira et al, 2022 ). The analysis revealed that curcumin exerts therapeutic effects on various tumor types, including the inhibition of tumor growth (SMD: −3.03; 95% CI: −3.84, −2.21; p < 0.00001), reduction in tumor volume (SMD: −7.30; 95% CI: −11.39,-3.21; p < 0.00001), and decrease in tumor weight (SMD: −3.96; 95% CI: −6.22, - 1.70; p = 0.0006).…”
Section: Discussionmentioning
confidence: 88%
“…Curcumin, a polyphenol derived from turmeric, is commonly used in culinary applications owing to its antioxidant, antimicrobial, and anti-inflammatory properties ( Hewlings and Kalman, 2017 ). A previous meta-analysis has demonstrated the therapeutic potential of curcumin for the treatment of malignant tumors ( de Oliveira et al, 2022 ). To date, there is a lack of published meta-analyses examining the efficacy of curcumin in PCa treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term release of curcumin from curcuminoids loaded (SLNs) can be up to 12 hours according to the Higuchi’s square root model [ 197 ]. According to the biological barriers in different diseases [ 198 ], kinds of nanomaterials were used to encapsulate curcumin forming nanoparticles, such as poly (lactic-co-glycolic acid) (PLGA) nanoparticles for cancer therapies [ 199 ], phenylboronic acid-conjugated chitosan nanoparticles [ 200 ], curcumin-loaded hybrid nano-particles (enzyme-targeted peptides, star-shaped polycyclic lipids) [ 201 ] and et al In addition, curcumin-loaded nanocapsules [ 202 ], nanocrystals [ 203 ], nanosphere [ 204 ], and nanomicelles were all attempted by researchers to improve curcumin’s pharmacokinetic parameters and achieved a certain degree of research progress. The emergence of nanomaterials not only improves the bioavailability of curcumin, but also improves the targeting and therapeutic effect of curcumin in different diseases.…”
Section: The Main Problems and Research Progress Of Curcumin In Clini...mentioning
confidence: 99%